Fabrication, Characterization of SiO2 Nanospheres and SiO2 Opal Photonic Crystals - Duy Thien, Nguyen; Tu, Nguyen Ngoc; Hoa, Nguyen Quang; Doanh, Sai Cong; Vu, Le Van (VNU Journal of Science: Mathematics - Physics, 2021)
In this report, we presented the usage of Stober method to fabricate SiO 2 nanospheres and self-assembly method to make SiO 2 opal photonic crystals based on the fabricated SiO 2 nanospheres. An averaged size of SiO 2 nanospheres was controlled by varying concentrations of NH 4 OH and TEOS. Crystal structure and morphology of particles was investigated by using X-ray diffraction (XRD) and scanning electron microscopy (SEM) techniques. Experimental results showed that SiO 2 nanospheres possess amorphous crystal structure with sizes ranged from 150 to 300 nm. The diffuse reflection spectra show the reflection peaks of the SiO 2 opal photonic crystals from 410 nm to 520 nm.